Impact of introducing integrated quality assessment for tuberculosis and malaria microscopy in Kano, Nigeria - Faruk Sarkinfada; Yunusa Aliyu; Charles Chavasse; Imelda Bates (Journal of Infection in Developing Countries)
Background: The World Health Organization (WHO) has recommended the integration of malaria microscopy quality assessment (QA) with that of other microscopically diagnosed diseases, but there is no evidence that it has been attempted. We assessed the feasibility of linking malaria microscopy into the existing tuberculosis (TB) microscopy QA system in Kano, Nigeria. Methodology: Five TB microscopy centres were selected for implementing the integrated TB and malaria microscopy QA scheme in the state. A model system was designed for selecting and blinded rechecking of TB and malaria slides from these laboratories. Supervision and evaluation was conducted at 3-month intervals for 24 months. Results: TB microscopy QA was strengthened in four laboratories. Full integration of the QA for TB and malaria microscopy was achieved in two laboratories, and partial integration in two other laboratories. The programme resulted in an increase in the specificity of both TB and malaria microscopy results. At the final assessment, 100% specificity was achieved for TB microscopy results in four laboratories. There was an increased concordance rate and decreased false positivity and false negativity rates of TB microscopy results in all five laboratories. Conclusions: It is feasible to integrate the QA system and training for TB and malaria microscopy for assessing and improving quality of both services. However, the integrated system needs testing in different settings in order to be able to develop sound recommendations to guide the complex scaling-up process.